Asuhan Keperawatan Pada An. R Dengan Demam Tifoid Di Ruang Mawar RSUD Banyudono - Pangestu, Agil Bagus, Irdawati S. Kep., Ns, Msi. Med (2015)
Background : Typhoid fever is a systemic infectious disease caused by the bacterium Salmonella Typhi. Until now typhoid fever remains a health problem in tropical countries including Indonesia. This disease usually affects the gastrointestinal tract, with symptoms of fever about a week, digestive disorders, and disorders of consciousness.Method : To know the nursing care in patients with typhoid fever that include assessment, intervention, implementration, and evaluation.Results : After the 3x24 hour nursing care for the authors found three nursing diagnoses, that is : increase in body temperature assosiated with the inflammatory process, acute pain associated with the disease process, changes in nutrition less than body requirements related to anorexia.Conclusion : for the treadment of patients with typhoid fever, there must be cooperation between health workers with families to always provide information about the development of the patients health, the patients family sould always motivated and always maintain the health of the patients lifestile. Keywords : Typhoid Fever, body temperature, acute pain, nutrition.